The effect of socio-scientific issue (SSI) based discussion: A student-centred approach to the teaching of argumentation - Nahid Parween Anwar; Muhammad Abid Ali (SOTL in the South, 2020)
Students should have the capability to argue about controversial science issues that are relevant to them and that impact society. These controversial issues, called socio-scientific issues (SSI), are influenced by social, ethical and moral norms. In current science education platforms, student-centred teaching strategies based on constructivism, are recommended to engage students in the construction of knowledge. Using a quantitative design, the present study sought to explore the efficacy of an argumentation-based teaching intervention about SSIs in an undergraduate classroom. It assessed students’ gains in the skill of argumentation. A one-group pre-test-post-test design was used. Data were generated through collection of students’ writing pre- and post-instruction, which was analysed using Toulmin’s Argumentation Pattern (TAP). Results reveal that almost half of the students reached a high level of argumentation. Findings show the importance of teaching content through learner-centred pedagogies. Introduction of various socio-scientific case studies and practicing argumentation has positively impacted on students’ argumentation skills. This study is significant for teachers as it provides an example to replicate in their classroom and can assist science teachers to enrich teaching and learning. The study recommends improving teachers’ competence in order to promote argumentation skills among students.